The Exploration of Biology Teacher's Perspective: The Utilization of Augmented Reality in Education: Eksplorasi Perspektif Guru Biologi: Pemanfaatan Augmented Reality Dalam Pendidikan - Solehah Nurwendah, Anisa; Harahap, Sahrona; Jayanto, Pery; Dwiningtyas Putri, Meirin (Jurnal Biogenerasi, 2025)
This study aims to explore the perception of Biology teachers towards Augmented Reality (AR)-based learning in the context of education. AR-based learning offers an interactive and immersive learning experience, which can improve understanding of difficult concepts as well as enrich students' experience in the learning process. However, the adoption of this technology in the classroom requires good readiness and understanding from the teacher. This study uses a qualitative approach with semi-structured interviews and Focus Group Discussions (FGD) with 16 Biology teachers. The data analysis used used was the thematic analysis method. The results of the study show that most teachers consider AR as a very potential tool to increase student motivation and engagement. Teachers also report that AR allows for the visualization of abstract concepts in a more tangible and engaging way. There are several obstacles such as limited infrastructure, lack of training, and difficulties in integrating AR into the curriculum. This research provides important insights for the development of technology education and training policies for teachers in order to support the implementation of AR-based learning more broadly. Keywords: augmented reality ; biology; education ; perception